The axe had never sounded Place, people and heritage of Recherche Bay, Tasmania - Mulvaney, John (Aboriginal History Monograph, 2007)
'This book meets well the triple promise of the title - the inter-connections of place, people and heritage. John Mulvaney brings to this work a deep knowledge of the history, ethnography and archaeology of Tasmania. He presents a comprehensive account of the area's history over the 200 years since French naval expeditions first charted its coastlines. The important records the French officers and scientists left of encounters with Aboriginal groups are discussed in detail, set in the wider ethnographic context and compared with those of later expeditions. 'The topical issues of understanding the importance of Recherche Bay as a cultural landscape and its protection and future management inform the book. Readers will be challenged to consider the connections between people and place, and how these may constitute significant national heritage.' Professor Isabel McBryde, AO, FRAI, FAHA, FSA The Australian National University